CALISTA: Enhancing digital trade infrastructure with value-added services - BHATTACHARYA, Shantanu (Institutional Knowledge at Singapore Management University, 2022)
Set in June 2021, the case documents the evolution and outcomes of CALISTA, a trade facilitation platform launched by Global eTrade Services (GeTS), Singapore, in 2018. With an affordable subscription model, CALISTA aided smooth trade flow by enabling single window management of the compliance, logistics, and trade finance. The COVID-19 pandemic disrupted international trade flows and altered consumer behaviour, spurring the boom of eCommerce. The scenario prompted the trade community to embrace trade automation in its quest for predictability, visibility and efficiency. Consequently, CALISTA’s sales nearly doubled. However, driven by a legacy mindset, many SMEs were still doing trade the old-fashioned way. Kok Keong Chong, the Chief Executive Officer of GeTS, wondered how he could bring on board more customers to CALISTA. By analysing the case, students would learn to 1) leverage Single Window Systems for efficient delivery and access to public services, develop viable digital platforms, 2) build scalable infrastructure using digital platforms, 3) foster tacit public-private partnerships to co-create infrastructure, 4) use digital platforms to achieve market access, efficiency, growth and sustainability, and 5) evaluate the efficiency of business models from the perspective of different stakeholders using Business Model Canvas.